1992
DOI: 10.1159/000126148
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Differences among Luteinizing Hormone Releasing Hormone Neurons from Postpartum and Estrous Cycling Cows

Abstract: Deficiency in secretion of luteinizing hormone releasing hormone (LHRH) from the median eminence (ME) is one of the factors limiting reinitiation of estrous cycles following parturition in cows. This study employs quantitative light microscopy to describe morphological changes in LHRH neurons obtained from cows at three postpartum times. Tissues were obtained from anestrous early postpartum (EPP; days 10-16, n = 5), midpostpartum (MPP; days 33-43, n = 4), and multiparous cycling (CYC; months 12-14, n = 4) cows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

1992
1992
1998
1998

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Finally, suckled anestrous cows had higher concentrations of opioid binding sites in tissue ho mogenates containing the preoptic-anterior hypothal amic regions than suckled cows that reinitiated estrous cycles [21 ]. In a companion study [23], we found in these same cows that LHRH dendritic lengths and ME innervation by LHRH axons and terminals were both reduced in EPP cows compared to CYC cows. In this study, irp-END was lowest in the ARC of EPP cows.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Finally, suckled anestrous cows had higher concentrations of opioid binding sites in tissue ho mogenates containing the preoptic-anterior hypothal amic regions than suckled cows that reinitiated estrous cycles [21 ]. In a companion study [23], we found in these same cows that LHRH dendritic lengths and ME innervation by LHRH axons and terminals were both reduced in EPP cows compared to CYC cows. In this study, irp-END was lowest in the ARC of EPP cows.…”
Section: Discussionmentioning
confidence: 61%
“…[32,33] and about 30% bind P4 [34]. These findings may account for the vast heteroge neity in POMC mRNA levels among individual ARC neurons following steroid treatments [35,36], In postpar tum cows, similar heterogeneity may have masked differ ences of POMC mRNA levels between suckled and nonsuckled cows [37], Possibly, an individual cell analysis, such as performed for LHRH neurons in the postpartum cow [23], might have revealed additional differences in ir-P-END neurons between postpartum groups. EPP MPP CYC Postpartum interval Previous studies demonstrated that the ME contains specific opioid binding sites and is a site of opioid inhibi tion of LHRH secretion [22], In postpartum cows, as pre viously described in heifers [20], ir-p-END in ME formed a well-defined band in the external layer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…El número de neuronas y fibras GnRH en los mamíferos es escaso y existen variaciones en diferentes especies de animales (81, 107-109, 115, 116), las mutaciones genéticas (122), el período de desarrollo (106,(108)(109)(110), el sexo (118,121,123), la estación reproductiva en especies cuya reproducción es estacional (124) y diferentes acontecimientos reproductivos tales como la ciclicidad, el parto y el puerperio, entre otros (125) son posibles causas para explicar estas diferencias. También, la distribución de los somas neuronales y los axones GnRH difieren notoriamente en las áreas y núcleos de la región hipotalámica entre las diferentes especies animales.…”
Section: Localización Y Número De Las Neuronas Gnrh Hipotalámicasunclassified
“…En la hembra bovina (Bos taurus), el porcentaje del área ocupado por las fibras GnRH-ir en la eminencia media fue significativamente menor en las vacas durante el período puerperal temprano con respecto a las hembras que se hallaban en el período puerperal tardío y al grupo de hembras cíclicas (125).…”
Section: Localización Y Número De Las Neuronas Gnrh Hipotalámicasunclassified